2007
DOI: 10.1021/ic700580u
|View full text |Cite
|
Sign up to set email alerts
|

Electron Exchange Involving a Sulfur-Stabilized Ruthenium Radical Cation

Abstract: Half-sandwich Ru(II) amine, thiol, and thiolate complexes were prepared and characterized by X-ray crystallography. The thiol and amine complexes react slowly with acetonitrile to give free thiol or amine and the acetonitrile complex. With the thiol complex, the reaction is dissociative. The thiolate complex has been oxidized to its Ru(III) radical cation and the solution EPR spectrum of that radical cation recorded. Cobaltocene reduces the thiol complex to the thiolate complex. The 1H and 31P NMR signals of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Whereas Norton et al [24] reported only one 31 P NMR signal (of PPh 3 , δ = −4 ppm) for a CDCl 3 solution of [RuCl 2 (PPh 3 ) 3 ], we observed a more complex 31 P NMR spectrum of a CDCl 3 solution of our product. In addition to the main signal at 41.0 ppm (which was very broad) we observed a signal of PPh 3 and two sets of dublets (both of them characteristic of cis-situated Rubound PPh 3 groups).…”
Section: Synthesis Of [Rucl 2 (Pph 3 ) 3 ]contrasting
confidence: 73%
See 2 more Smart Citations
“…Whereas Norton et al [24] reported only one 31 P NMR signal (of PPh 3 , δ = −4 ppm) for a CDCl 3 solution of [RuCl 2 (PPh 3 ) 3 ], we observed a more complex 31 P NMR spectrum of a CDCl 3 solution of our product. In addition to the main signal at 41.0 ppm (which was very broad) we observed a signal of PPh 3 and two sets of dublets (both of them characteristic of cis-situated Rubound PPh 3 groups).…”
Section: Synthesis Of [Rucl 2 (Pph 3 ) 3 ]contrasting
confidence: 73%
“…Following literature methods [24,25], which report the synthesis of [RuCl 2 (PPh 3 ) 3 ] from commercial RuCl 3 ⋅ 3H 2 O, we prepared [RuCl 2 (PPh 3 ) 3 ] from elemental Ruthenium without isolating the intermediate Ru(III)-chloride: A mixture of Ruthenium powder (0.750 g, 7.42 mmol), NaOH (4.00 g, 100 mmol) and NaClO 3 (2.63 g, 24.7 mmol) was cautiously heated in a crucible (using a Bunsen burner) for 15 min (until the evolution of gas from the deep red melt ceased). The mixture was allowed to cool to ambient temperature and was then dissolved in conc.…”
Section: Synthesis Of [Rucl 2 (Pph 3 ) 3 ]mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar 31 P NMR spectroscopic behavior has been reported for compounds [{(η 6 ‐ p ‐cymene)RuClN 3 } 2 (μ 2 ‐dppe)] [ δ = 26.7 (d)],7a [{(η 6 ‐C 6 Me 6 )RuXN 3 } 2 (μ 2 ‐dppe)] [X = N 3 , δ = 31.1],7b [X = Cl, δ = 30.3],7b [(η 6 ‐C 6 H 6 )RuCl 2 ] 2 (μ 2 ‐dppe) [ δ = 23.3 (s)],7c [{CpRu(N 3 )} 2 (μ 2 ‐dppe) 2 ] [ δ = 39.19],8a [{CpRuCl} 2 (μ 2 ‐dppe) 2 ] [ δ = 37.10],8a and [{CpRu(SnCl 3 ) 2 } 2 (μ 2 ‐dppe)] [ δ = 43.5 (s)],8b as well as three intermediates species observed in the phosphine substitution reactions between CpRuCl(PPh 3 ) 2 and dppe: CpRuCl(PPh 3 )(κ 1 ‐dppe) [ δ = 41.51 (d), –12.10],8a CpRuCl(κ 1 ‐dppe) 2 [ δ = 40.72 (d), –12.31],8a and [{CpRuCl(PPh 3 )} 2 (μ 2 ‐dppe)] [ δ = 43.11 (d), 42.76 (d)] 8a. In agreement with the presence of a bridging dppe ligand in compound 5 , the 31 P NMR shows an upfield shift compared to complexes where the dppe is acting as a chelate in mononuclear ruthenium derivatives, such as: [(η 6 ‐C 6 H 6 )Ru(κ 2 ‐dppe)Cl]Cl [ δ = 70.4 (s)],7c CpRuCl(κ 2 ‐dppe) [ δ = 79.9],9 [CpRu(L)(κ 2 ‐dppe)]BPh 4 [ δ = 78.3–82.9],9 Cp*RuX(κ 2 ‐dppe) [X = Cl, δ = 73.5–74.6],10,11 [X = N 3 , δ = 75.7],11 [X = H, δ = 90.2],12 [Cp*RuX(κ 2 ‐dppe)]BF 4 [X = (H) 2 , δ = 71.3, (η 2 ‐H 2 ), δ = 77.4],12 and CpRu(κ 2 ‐dppe)SnCl 3 [ δ = 77.8 (s)],8b or dinuclear compounds where the bidentate dppe is also coordinated only to one metal atom, such as {Cp(PPh 3 ) 2 Ru}C≡C‐C≡C{Ru(κ 2 ‐dppe)Cp} δ = 86.1 and {Cp(κ 2 ‐dppe) 2 Ru}C≡C‐C≡C{Ru(κ 2 ‐dppe)Cp} δ = 86.7 ppm 13…”
Section: Resultsmentioning
confidence: 99%
“…For drying dichloromethane, CaH 2 was used as drying agent whereas for toluene, n-hexane, n-pentane and 1,4-dioxane, sodium was employed as drying agent and benzophenone was used as indicator. The compounds RuCl 2 (PPh 3 ) 3 [34], 4-methyl-3-phenyl-1-pentyn-3-ol [23], 4,4-dimethyl-3-phenyl-1-pentyn-3-ol [24], 1-cyclohexyl-1-phenyl-2-propyn-1-ol [25] and (1-(allyloxy)prop-2-yne-1,1-diyl)dibenzene [35] were prepared according to the literature. n-Hexane, n-pentane, 1,4-dioxane and toluene were purchased from Fiers.…”
Section: General Considerationmentioning
confidence: 99%